2020
DOI: 10.1080/0284186x.2020.1794033
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating lymphocyte grade in Merkel cell carcinoma: relationships with clinical factors and independent prognostic value

Abstract: Introduction: Surrogate markers of the host immune response are not currently included in AJCC staging for Merkel cell carcinoma (MCC), and have not been consistently associated with clinical outcomes. We performed an analysis of a large national database to investigate tumor infiltrating lymphocyte (TIL) grade as an independent predictor of overall survival (OS) for patients with MCC and to characterize the relationship between TIL grade and other clinical prognostic factors. Material and methods: The NCDB wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Paulson et al similarly found present TILs (relative to absent) to be associated with improved MCC-specific survival by univariable but not multivariable analysis in a retrospective study of 129 patients with MCC [ 44 ]. Yusuf and colleagues queried the NCDB and found both brisk and non-brisk TIL grade to be associated with decreased adjusted mortality hazard relative to absent TIL grade [ 45 ].…”
Section: Clinical and Prognostic Factorsmentioning
confidence: 99%
“…Paulson et al similarly found present TILs (relative to absent) to be associated with improved MCC-specific survival by univariable but not multivariable analysis in a retrospective study of 129 patients with MCC [ 44 ]. Yusuf and colleagues queried the NCDB and found both brisk and non-brisk TIL grade to be associated with decreased adjusted mortality hazard relative to absent TIL grade [ 45 ].…”
Section: Clinical and Prognostic Factorsmentioning
confidence: 99%
“…Tumor-infiltrating lymphocytes are independent predictors of anterior lymph node status and survival in cancer [ 24 ]. We investigated whether this gene expression correlated with the level of immune infiltration in different types of cancers.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the validated hub genes could influence metastasis of BRCA1/2 -MUT BC through mechanisms including regulation of immune response, cell cycle, cell migration, and metabolic processes. Many recent studies have demonstrated that tumor-infiltrating immunocytes (TICs) can regulate and participate in the TME, regulate tumor progression, and influence lymph node metastasis and prognosis ( Azimi et al, 2012 ; Yusuf et al, 2020 ). Thus, we used the TIMER web server and CIBERSORT to assess immune infiltration and its correlations with BRCA1 / 2- associated hub genes.…”
Section: Resultsmentioning
confidence: 99%